Are entrepreneurs' decisions more biased? An experimental investigation of the susceptibility to status quo bias - Burmeister, Katrin; Schade, Christian (Journal of Business Venturing, 2007)
Entrepreneurship research has demonstrated that entrepreneurs are more susceptible to certain cognitive biases than are selected other individuals. We investigate whether this finding holds for the status quo bias not yet investigated in the entrepreneurship literature. The status quo bias is defined as the tendency to select a previously chosen alternative disproportionately often. We compare entrepreneurs' decisions with those of students and bankers in an experimental study. We find that entrepreneurs are as affected by the status quo as students but less affected than bankers. Accounting for differences in experience and types of decision scenarios, we have indirect evidence for a consistency of entrepreneurs' decisions with what would be expected from a stereotypical Schumpeterian entrepreneur: being more open to new options than other individuals are. However, since entrepreneurs are frequently influenced by the status quo, we discuss the pros and cons of such behavior.